1997
DOI: 10.1088/0268-1242/12/6/019
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of surface damage in dry-etched InP

Abstract: Sn-doped InP wafers were etched by reactive ion beam etching (RIBE) using a gas mixture of N 2 /O 2 at ion energies varying from 100 to 600 eV. We investigated the radiation damage caused by RIBE using various techniques which are sensitive to the near-surface region. The optical and electrical properties of the damaged layer as a function of ion energy were studied by photoluminescence microscopy (PLM), photoluminescence spectroscopy, spectroscopic ellipsometry (SE) and electrochemical capacitance-voltage pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2000
2000
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…5,6 A great effort has been made to reduce the ion irradiation damage during dry etching of compound semiconductors and other related processes. 3,[21][22][23] Using deep level transient spectroscopy to detect defect states, Yu et al, 20 investigated defect formation on GaAs induced by an exposure of the sample to an argon plasma with a sample biasing voltage to facilitate ion irradiation. They concluded that damage-free ion beam processing is possible with an ion energy of less than 20 eV.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 A great effort has been made to reduce the ion irradiation damage during dry etching of compound semiconductors and other related processes. 3,[21][22][23] Using deep level transient spectroscopy to detect defect states, Yu et al, 20 investigated defect formation on GaAs induced by an exposure of the sample to an argon plasma with a sample biasing voltage to facilitate ion irradiation. They concluded that damage-free ion beam processing is possible with an ion energy of less than 20 eV.…”
Section: Introductionmentioning
confidence: 99%
“…The surface of an etched material is admitted to increase the probability of non-radiative electron-hole recombination (as it can be explained by the increase of the SRV). This is due to the damage induced on the surface by the etching together with the point defects created at the surface neighbourhood by the ion bombardment [3]. The lower CL intensity on the ridge can arise from the strong increasing of the SRV at the side walls; the carriers generated inside the ridges have a non-negligible probability of reaching the sidewalls and to recombine therein non-radiatively; this probability should depend on the ridge width, the narrower the ridge the higher the probability of minority carriers to reach the ridge sidewalls recombining non-radiatively.…”
Section: Resultsmentioning
confidence: 99%
“…The studies carried out for the optimisation of the etching procedures have been mainly focused on the morphological analysis, e.g. the verticality of the engraved walls, and the residual roughness [3,4]. These studies are currently carried out by morphology inspection techniques, as scanning electron microscopy (SEM) and atomic force microscopy (AFM).…”
Section: Introductionmentioning
confidence: 99%
“…The curve is related to the DX centres filled with electrons in the λ region. Curves (2) and (3) are thermal scans for the samples under zero-bias corresponding to initial conditions at 80 K of empty DX centres. Initial condition (3) was obtained by cooling the samples from 300 to 80 K with -9 V. At 80 K the bias was returned to 0 V. Condition (2) was obtained by cooling the samples with zero bias and then emptying the DX centres by recombination of the electrons with injected holes under forward bias (+2 V/ 5 min).…”
Section: Resultsmentioning
confidence: 99%
“…Due to anisotropic properties and consequently good linewidth control, "dry etching" is useful in pattering semiconductor properties including etching sub-micron features both in Si and III-V semiconductors [1][2][3]. For instance, dry etching is used for the fabrication of advanced optoelectronic components like quantum wires and quantum dots [4].…”
Section: Introductionmentioning
confidence: 99%